FEASIBILITY STUDY ANALYSIS OF BUSINESS MINGGON TOURISM MARKET, JATINAN, BATANG DISTRICT - Wardah Mahirdini (Akademi Pariwisata Bunda Mulia, 2023)
Culinary tourism is a form of tourism that focuses on food as an attraction for exploration and tourism purposes.